Investigation of the mechanism of Fe2Al5 powder into FeAl powder transformation. Issue 1 (January 2019) - Khoshhal, Razieh; Hosseinzadeh, Ali
Abstract : In the iron aluminide production process from the elementary powders, it is confirmed that Fe2 Al5 powder forms at lower temperatures and turns to FeAl at high-temperatures. Though there are some theories about the Fe2 Al5 to FeAl transformation mechanism, these assumptions have not been proven in any practice. Therefore, the purpose of this research is to clarify the Fe2 Al5 to FeAl transformation mechanism. To achieve this goal, the samples with the ratio of 1:1 of iron and aluminum were heat treated. It was found that Fe2 Al5 forms at 700 °C and converts to FeAl at 900 °C. The Fe2 Al5 to FeAl transformation mechanism was clarified at the next step. It was shown that the direct transition of Fe2 Al5 to FeAl is not possible. Therefore, a third factor should be involved. Iron was predicted as the third factor which helps Fe2 Al5 to convert into FeAl. This hypothesis was proved in practice.